Serum soluble Fas ligand is a severity and mortality prognostic marker for COVID-19 patients - Saleki, Kiarash; Shirzad, Moein; Javanian, Mostafa; Mohammadkhani, Sheyda; Alijani, Mohammad Hossein; Miri, Niloufarsadat; Oladnabi, Morteza; Azadmehr, Abbas (Frontiers in Immunology, 2022)
Finding cytokine storm initiator factors associated with uncontrolled inflammatory immune response is necessary in COVID-19 patients. The aim was the identification of Fas/Fas Ligand (FasL) role in lung involvement and mortality of COVID-19 patients. In this case-control study, mild (outpatient), moderate (hospitalized), and severe (ICU) COVID-19 patients and healthy subjects were investigated. RNA isolated from PBMCs for cDNA synthesis and expression of mFas/mFasL mRNA was evaluated by RT-PCR. Serum sFas/sFasL protein by ELISA and severity of lung involvement by CT-scan were evaluated. Also, we docked Fas and FasL via Bioinformatics software (in silico) to predict the best-fit Fas/FasL complex and performed molecular dynamics simulation (MDS) in hyponatremia and fever (COVID-19 patients), and healthy conditions. mFasL expression was increased in moderate and severe COVID-19 patients compared to the control group. Moreover, mFas expression showed an inverse correlation with myalgia symptom in COVID-19 patients. Elevation of sFasL protein in serum was associated with reduced lung injury and mortality. Bioinformatics analysis confirmed that blood profile alterations of COVID-19 patients, such as fever and hyponatremia could affect Fas/FasL complex interactions. Our translational findings showed that decreased sFasL is associated with lung involvement; severity and mortality in COVID-19 patients.We think that sFasL is a mediator of neutrophilia and lymphopenia in COVID-19. However, additional investigation is suggested. This is the first report describing that the serum sFasL protein is a severity and mortality prognostic marker for the clinical management of COVID-19 patients.